Developing a diagnostic assay for Pneumocystis jirovecii pneumonia and investigating the interaction of Pneumocystis murina and respiratory syncytial virus during co-infection in mice - Hlagala, Elizabeth (Department of Pathology, 2025)
Pneumocystis pneumonia (PCP) is an AIDS-defining illness that is caused by an opportunistic fungal pathogen, Pneumocystis jirovecii. In immunocompromised individuals, P. jirovecii can result in fatal pneumonia, and healthy individuals can be reservoirs for P. jirovecii. PCP places a significant strain on the healthcare system, resulting in high rates of mortality and morbidity. Diagnosis of PCP remains a challenge since Pneumocystis species cannot reliably be cultured in vitro. The current methods of diagnosis are invasive, expensive, lack specificity and sensitivity and are not readily available in low-resource settings. To reduce the burden of disease, a reliable diagnostic test is necessary. Additionally, co-infections are common, especially in immunocompromised individuals, and are often linked to increased severity. In the Drakenstein Child Health Study, respiratory syncytial virus (RSV) was the most prevalent cause of pneumonia in children under 5 years. Furthermore, seroprevalence studies reveal that the majority of children under 4 years would have been exposed to P. jirovecii, suggesting that exposure to both organisms occurs simultaneously. The interaction between RSV and P. jirovecii and the associated effect on mediating cross-protective effects on host immunity remain poorly understood. In this study we evaluated a polyclonal antibody (pAb) raised against a putative Pneumocystis biomarker (Kex1), with the outlook of developing a lateral-flow assay (LFA) for rapid point-of care diagnosis of PCP. Kex1 is an antigenically stable serine protease highly conserved across Pneumocystis species. Proof-of-principle experiments investigated the presence of Kex1 in mice experimentally infected with P. murina using pAb-based immunoassays. Protein samples from naïve and infected mouse lungs were analysed using Western blot and dot blot to confirm the presence of Kex1. Using the pAb at a dilution of 1/20,000, a protein of approximately 100 kDa was detected in the infected lung and serum samples, but not in naïve samples. Lastly, using a mouse model of P. murina and RSV coinfection, we investigated the effects of P. murina on viral pneumonia. Wild-type and immunocompromised RAG-1-deficient mice were infected with P. murina followed by RSV and the disease parameters were investigated. RT qPCR analysis demonstrated that P. murina infection reduced RSV burden in coinfected mice compared to RSV-only mice. Pro-inflammatory cytokines IL-1β, IL-12 p40, IL12-p70, and IFN γ and serum IgM and IgG levels were elevated in the P. murina group compared to the RSV group. Interestingly, the levels of IFN-β were significantly reduced in the coinfected group compared to the RSV group. The detection of Kex1 in infected mouse lungs, urine, and serum of P. murina-infected mice makes it a promising tool for the rapid diagnosis of PCP. Urine and serum offer less invasive and inexpensive methods of diagnosing PCP. Pneumocystis murina reduces the burden of RSV during coinfection in both Wild-type and RAG-1-deficient mice. This may be due to the increased pro-inflammatory response, mucous production, and antibody response during primary P. murina infection, which primes the immune system towards a T-helper type-2 immune response against RSV. The observed decrease in IFN-β levels in the co-infected group suggests that the reduced RSV burden may not be solely a consequence of antiviral cytokines, but rather the result of other immune mediators activated during the primary P. murina infection.